Flow visualization in dilute oxide based nanofluid boiling - Patra N.; Ghosh P.; Singh R.S.; Nayak A. (My University, 2025)
Nanofluids are known for better heat transfer characteristics in many heat transfer devices due to their enhanced heat transfer abilities. In this work, an experimental study of forced convective flow boiling was conducted for Al2O3-water and SiO2-water nanofluids through a vertical transparent quartz channel. Thermal-hydraulic phenomenon of water and nanofluids have been investigated experimentally through high speed visualization. The boiling heat transfer characteristics were measured and the effect of nanoparticles on heat transfer coefficient were studied. The heat transfer coefficient was found to be enhanced at lower concentration of nanofluids as compared to pure water and decreased with increasing nanoparticle concentration. Distinctly different bubble dynamics were observed with water and nanofluids under different heat fluxes. Images revealed that, at lower heat flux, bubbles nucleated and grew while sliding without remarkable influence of other bubbles in case of water as well as nanofluids. However, with increasing heat flux, the presence of sliding bubbles affected the nucleating bubbles due to coalescence and the effect was more prominent in water exhibiting smaller number of larger bubbles as compared to nanofluids. These larger bubbles united to form vapor slugs which led to flow oscillation and consequently forming dry patch on heater surface. Nanofluids inhibited and delayed the development of dry patch on the heater surface because of continuously sustained miniature bubbles in the flow as observed. Moreover, with the increasing heat flux, the amplitude of oscillation was less in nanofluids and the transition occurred very slowly. © 2019